(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of physical therapy in treating constipation in stroke patients at the Rehabilitation Department, 108 Military Central Hospital.Materials and Methods: A prospective, non-controlled clinical intervention study was conducted on 32 stroke patients with constipation symptoms, treated at the Rehabilitation Department, 108 Military Central Hospital from December 2024 to May 2025. Patients received: abdominal massage, pelvic floor and abdominal muscle strengthening exercises, and electrical stimulation of the pelvic floor muscles Results: Among constipated patients, 68.75% had ischemic stroke and 21.25% had hemorrhagic stroke. After intervention, defecation frequency increased from 2.1 ± 0.7 to 4.8 ± 0.9 times/week (p<0.001), defecation time decreased from 15.3 ± 5.2 to 7.4 ± 2.6 minutes (p<0.001), and the Bristol score improved from 1.8 ± 0.8 to 3.7 ± 0.7 (p<0.001). Quality of life measured by SF-36 significantly increased from 42.9 ± 13.9 to 60.5 ± 11.6 points (p<0.001), with improvements across all 8 domains. The majority of patients (84.4%) were satisfied with the intervention outcomes.Conclusion: Physical therapy is an effective method for treating constipation in stroke patients, significantly improving defecation frequency and quality, while enhancing patients’ overall quality of life.